City for all? A geospatial approach to equity, sustainability, and gentrification in Seattle, Washington. - Welch, Nicolas. (2017)
Abstract: Seattle is at a crossroads. Despite ambitious plans for sustainability and equitable development, there is no consensus about how to achieve these two seemingly compatible goals. A recent period of considerable economic and population growth has led to rising rents and home values. As a result, gentrification is a significant concern. Recent research has sought to use geospatial analysis to identify areas that are vulnerable to gentrification and displacement. These studies vary in the methodology they employ. This thesis reviews previous efforts to measure gentrification susceptibility using GIS, assesses their strengths and weaknesses, and proposes an improved methodology for Seattle. The results of this new approach show that the neighborhoods most vulnerable to gentrification are First Hill, the Central District, Columbia City, High Point, and Northgate.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Julian Agyeman.; Committee: Barbara Parmenter.; Keywords: Urban planning, Sustainability, and Geographic information science and geodesy.